2019
DOI: 10.1177/0961203319845476
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of IL-24 in systemic lupus erythematosus patients

Abstract: Objective This study aimed to assess IL-24 levels and their association with clinical manifestations in patients with systemic lupus erythematosus (SLE). Methods There were 75 patients with SLE and 58 healthy controls recruited in this study. Serum levels of IL-24 were measured by enzyme-linked immunosorbent assays, and mRNA levels of IL-24 were tested by quantitative real-time polymerase chain reaction . The area under the curve of the receiver operating characteristic (ROC) curve was used for diagnostic abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous studies found elevated serum level of IL-19 in patients with diabetic nephropathy [7]. Moreover, positive correlation was demonstrated between serum IL-24 level and the severity of lupus nephritis and renal ischemic/ reperfusion injury [8,17]. Considering the above data strongly implies the role of the IL-20 subfamily in the pathomechanism of different renal diseases.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous studies found elevated serum level of IL-19 in patients with diabetic nephropathy [7]. Moreover, positive correlation was demonstrated between serum IL-24 level and the severity of lupus nephritis and renal ischemic/ reperfusion injury [8,17]. Considering the above data strongly implies the role of the IL-20 subfamily in the pathomechanism of different renal diseases.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, connection between IL-20 subfamily of cytokines and CKD has been proposed. Indeed, increased serum level of IL-19 and IL-24 was demonstrated in diabetic nephropathy and lupus nephritis [7,8]. Furthermore, our previous genome-wide analysis performed on new-born rat kidneys suggested the possible role of IL-24 in the renal tissue remodeling, as well [9].…”
Section: Introductionmentioning
confidence: 91%
“…A previous study 164 showed that IL‐19 level was slightly increased in SLE patients compared with healthy individuals. Another study 165 also found that IL‐24 level was significantly elevated and correlated with disease activity in SLE patients. However, there was another report showed that no difference was found in serum IL‐24 levels between SLE patients and healthy individuals 164,166 .…”
Section: Introductionmentioning
confidence: 85%
“…It is characterized by the production of autoantibodies—including anti-nuclear (ANAs), anti-double-stranded DNA (dsDNA), anti-Smith antigen (Sm), and anti-ribonucleoproteins (RNP)—against the self-antigen from cell nuclei. IL-24 serum levels are significantly higher in patients with SLE compared with healthy individuals, and elevated IL-24 levels are also associated with disease severity [ 53 ]. However, no significant difference in IL-24 serum levels was observed between SLE patients and healthy controls in two other independent studies [ 39 , 54 ].…”
Section: Il-24 In Inflammatory and Autoimmune Diseasesmentioning
confidence: 99%